Potential of Guava (Psidium guajava L.) Leaf Extract as Antioxidant Agent in Natural Mud Mask Formulation - Mardiana, Rosa; Salsabila, Salsabila; Lidyawati, Lidyawati (Serambi Journal of Agricultural Technology, 2025)
This study aimed to determine the antioxidant activity of guava (Psidium guajava L.) leaf extract and its potential use as an active ingredient in a natural mud mask formulation. The research employed an experimental laboratory design with a single factor, namely variations in guava leaf extract concentrations (0 g, 3 g, and 5 g). The antioxidant activity was evaluated using the DPPH method, and the results were expressed as IC₅₀ values. The findings revealed that the antioxidant activity increased significantly with the concentration of guava leaf extract. Formula F0 (without extract) exhibited very weak activity with an IC₅₀ value of 210 ppm, while F1 (3 g extract) and F2 (5 g extract) showed very strong activities with IC₅₀ values of 1.165 ppm and 0.541 ppm, respectively. These results indicate that guava leaf extract has very strong antioxidant potential, comparable to vitamin C (IC₅₀ = 0.481 ppm). Therefore, the formulation containing 5 g of guava leaf extract is considered optimal for developing a safe, effective, and environmentally friendly natural clay mask with high antioxidant potential.